Fractografia quantitativa e o conceito de tenacidade à fratura para a análise do efeitodo choque térmicos em TiO2 - Prado, Camila Cristina Silva do [UNESP] (2012)
The present study evaluated the use of semicircular bending test (SCB) as an alternative to conventional bending test to examine the effect of thermal shock. Still, studies the behavior of fracture surfaces generated by monofractal behavior analysis, which allows us to evaluate the contributions of the microstructure and the mechanical context in forming reliefs during the crack propagation. The fractal analysis is made from elevation maps obtained by reconstruction method by extension of the focus stacks of digital images acquired in microscope. The specimens used were samples semicircular pressed TiO2 (rutile) with and without heat shock, prepared for testing mode I loading. Were also produced, specimens in the form of bars for Weibull statistical analysis. From the three-point bending test, we found the variation of fracture toughness between the samples after the heat shock and natural condition. The SCB test was feasible for the analysis of thermal shock resistance. The results showed that the value of the fracture toughness decreases as the heat shock treatment